Bridging rigorous assessment of water availability from field to catchment scale with a parsimonious agro-hydrological model. (August 2017) - Van Gaelen, Hanne; Vanuytrecht, Eline; Willems, Patrick; Diels, Jan; Raes, Dirk
Abstract: While simple crop and hydrological models are limited with respect to the number and accuracy of the processes they incorporate, complex models have high demand for data. Due to the limitations of both categories of models, there is a need for new agro-hydrological models that simulate both crop productivity and water availability in agricultural catchments, with low data and calibration requirements. This study aimed at developing a widely applicable parsimonious agro-hydrological model, AquaCrop-Hydro, which couples the AquaCrop crop water productivity model with a conceptual hydrological model. AquaCrop-Hydro, simulating crop productivity, the daily soil water balance and discharge at the catchment outlet, performed well for an agricultural catchment in Belgium. The model can be used to investigate the effect of agricultural management and environmental changes from field to catchment scale in support of sustainable water management in agricultural areas. Graphical abstract: Highlights: AquaCrop-Hydro extends AquaCrop with a conceptual hydrological model. AquaCrop-Hydro requires a limited amount of data and calibration. AquaCrop-Hydro accurately predicts crop production and river discharge. Overland flow is predicted less accurate due to the model's daily time step. AquaCrop-Hydro is expected to be widely applicable.